Grandparenthood in China and Western Europe: An analysis of CHARLS and SHARE. (September 2020) - Zhang, Jing; Emery, Tom; Dykstra, Pearl
Abstract: Grandparenthood is a fascinating research area that not only brings together three generations and multiple roles in different life domains, but also echoes social contexts across historical times and places. Comparative research on grandparenthood, however, rarely includes non-western countries. This article seeks to answer the question of how grandparenthood differs between Western Europe and China by using comparable representative surveys of older adults. We extend the literature in two ways by showing that: 1) compared to Western Europe, becoming a grandparent occurs earlier and is virtually universal in both Urban and Rural China – the probability of being a grandparent is over 80% for Chinese by the time they are 55, while the same cannot be said for Western Europeans until they are aged between 70 and 80; and 2) the role-overlaps with grandparenthood are different for older Chinese and Western Europeans. The probability of being a working grandparent in Rural China is about twice that in Western Europe, while the rate is similar to Western Europeans for Urban Chinese. Chinese grandparents are also more likely to live with their children than Western Europeans. Conversely, as all family transitions come earlier for Chinese but life expectancy is shorter, the probabilities that grandparenthood overlaps with widowhood and filial roles are similar to that in Western Europe. Taken together, this study provides an overarching picture of the characteristics of grandparenthood in different societies that are fundamental to the meaning, performance, and impact of grandparental roles and relevant to a better understanding of grandparenthood worldwide.